2020
DOI: 10.1016/j.heliyon.2020.e05154
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Persian language person-centered climate questionnaire – Patient version (PCQ-P)

Abstract: Background Person-centered care is a valuable approach to improve the quality of care of the elderly and is a starting point for maintaining the dignity of people needing care. Objectives This study aimed at translation, cultural adaptation, and validation of the Persian version of the Person-centered Climate Questionnaire–Patient questionnaire in elderly patients admitted to the Eastern Guilan hospitals from 2017-2018. Design This research w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Based on the results of the study, the mean total score of PCC climate from the patients' point of view was 81.49 ± 7.14 out of 102, which indicates the high PCC climate in hemodialysis wards of the studied units. Kobrai-Abkenar et al [48] conducted a study to evaluate the PCC climate among patients admitted to internal medicine, surgery, and ENT wards. The mean total score of PCC in these units was 80.46 ± 5.62 which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the study, the mean total score of PCC climate from the patients' point of view was 81.49 ± 7.14 out of 102, which indicates the high PCC climate in hemodialysis wards of the studied units. Kobrai-Abkenar et al [48] conducted a study to evaluate the PCC climate among patients admitted to internal medicine, surgery, and ENT wards. The mean total score of PCC in these units was 80.46 ± 5.62 which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Kobrai-Abkenar et al [48] using the PCQ-P found that "in assessing the quality of health care from the patient's perspective, physical environmental factors such as well-groomed staff, neat and clean hospital environment, modern medical equipment, harmonious physical layout and appropriate signage, and the presence of windows are important. In addition to the known evidence that physical environmental factors such as a harmonious physical layout, appropriate signage, and windows are important in assessing the quality of health care from the patient's perspective," the PCQ-P items "a place where the staff talk to me (the patient) in a way that I can understand" and "a place where the staff make efforts to make me feel comfortable" scored high.…”
Section: Discussionmentioning
confidence: 99%